2016
DOI: 10.1124/dmd.115.067595
|View full text |Cite
|
Sign up to set email alerts
|

Considering Age Variation When Coining Drugs as High versus Low Hepatic Extraction Ratio

Abstract: The hepatic extraction ratio (E H ) is commonly considered an "inherent attribute" of drug. It determines the main physiological and biological elements of the system (patient attributes) that are most significant in interindividual variability of clearance. The E H

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 16 publications
8
30
1
Order By: Relevance
“…Due to the lower intrinsic hepatic clearance, the hepatic extraction ratio is very low in preterm neonates compared with adults, resulting in a much higher hepatic bioavailability than expected based on adult values. This has been previously reported by Salem et al . who found that the hepatic extraction ratio of midazolam increased with age.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Due to the lower intrinsic hepatic clearance, the hepatic extraction ratio is very low in preterm neonates compared with adults, resulting in a much higher hepatic bioavailability than expected based on adult values. This has been previously reported by Salem et al . who found that the hepatic extraction ratio of midazolam increased with age.…”
Section: Discussionsupporting
confidence: 85%
“…who found that the hepatic extraction ratio of midazolam increased with age. They found that the ontogeny of hepatic enzyme abundance and to a lesser extent the smaller number of microsomal protein per gram of liver contributed to the observed differences between preterm neonates and adults . Based on the hepatic intrinsic clearance, the hepatic blood flow, the fraction unbound in blood, and the blood:plasma ratio, the total plasma clearance can be calculated (Eq.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the developmental increase in OCT1 and UGT2B7 protein expression and hepatic blood flow in the Simcyp Simulator. Similar to this finding, it was reported that the hepatic extraction ratio of midazolam, a CYP3A probe substrate, varies with age due to age‐dependent physiological changes, including hepatic CYP3A4 protein expression . From these findings, the hepatic extraction ratio in children, especially for high extraction drugs, can be different from that in adults due to the developmental change in physiological factors over age.…”
Section: Discussionsupporting
confidence: 81%
“…47 Therefore, phenotypic and genotypic changes in CYP activity may partially explain the observed large PK variability of methadone in neonates and adults, which could be due to the low hepatic extraction ratio of methadone as observed in adults (ie, capacity-limited clearance). 48 In addition, AGP has been shown to increase during gestation and reach adult levels by 1 year of age. 35 These changes in protein binding could also contribute to methadone variability in neonates.…”
Section: Discussionmentioning
confidence: 99%